2005
DOI: 10.1103/physrevlett.95.155501
|View full text |Cite
|
Sign up to set email alerts
|

Amorphouslike Diffraction Pattern in Solid Metallic Titanium

Abstract: Amorphouslike diffraction patterns of solid elemental titanium have been detected under high pressure and high temperature using in situ energy-dispersive x-ray diffraction and a multianvil press. The onset pressure and the temperature of formation of amorphous titanium is found to be close to the --! triple point in the P-T phase diagram. Amorphous Ti has been found to be thermally stable up to 1250 C for at least 3 min at some pressures. By analyzing the conditions for producing amorphous elemental Zr and Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…5(a)), shows the presence of amorphous intermediate state. Experimental observations are beginning to support our findings, for example, amorphous-like structures have been observed in previous quasi-static DAC experimental measurements of pure Zr[21,38].…”
supporting
confidence: 86%
“…5(a)), shows the presence of amorphous intermediate state. Experimental observations are beginning to support our findings, for example, amorphous-like structures have been observed in previous quasi-static DAC experimental measurements of pure Zr[21,38].…”
supporting
confidence: 86%
“…Thus, amorphous-like energy-dispersive X-ray diffraction patterns (absence of Bragg spots) were earlier reported for solid hightemperature/high pressure zirconium and titanium [7,8], but later reconciled with rapidly grown crystalline grains [9] confirmed by intense Bragg spots in two-dimensional angle-dispersive X-ray diffraction spectra. Other studies on amorphous titanium concerned molecular dynamics simulation of crystallization [10] and amorphization of titanium by using C + , O + and Cr + ion implantation [11], oxygen-induced ball milling [12] and cryorolling combined with surface mechanical attrition treatment [13].…”
Section: Introductionmentioning
confidence: 61%
“…The deposited diffraction-less Ti coats are stable at ambient temperatures for extended periods of time (more than a year). This is very different from the amorphous-like Ti phases observed at high pressures and temperatures which rapidly revert to the crystalline phase upon cooling to room temperature [8]. The base pressure during the present ablative conditions being by 2 orders of magnitude lower than in our previous experiments [31] should lead to a much smaller in situ formation of Ti suboxides due to less air leakage in the course of the ablative deposition process.…”
Section: Discussionmentioning
confidence: 82%
“…Amorphization in nonmetallic elements, such as gallium [19], silicon [21], germanium [22], and selenium [23], is easily achievable. However, some studies reported amorphous phases in metallic titanium [24], nickel [25], and cobalt [26,27] produced via nonequilibrium processing. Among the nonequilibrium techniques, mechanical milling (MM) is a well-known process for producing a wide range of novel materials with unique properties.…”
Section: Introductionmentioning
confidence: 99%